2013
DOI: 10.1186/ar4364
|View full text |Cite
|
Sign up to set email alerts
|

Sialoadhesin deficiency does not influence the severity of lupus nephritis in New Zealand Black x New Zealand White F1 mice

Abstract: IntroductionSystemic lupus erythematosus (SLE) is a chronic inflammatory condition with multisystem involvement. One of the key features of the disease is the upregulation of type I interferons, resulting in the so-called “interferon signature”. Recent flow cytometric and transcriptomic studies identified Sialoadhesin (Sn, CD169) as an important interferon-induced blood monocyte biomarker in diseased patients. To investigate a potential causative role of Sn in SLE, we generated NZBWF1 (New Zealand Black x New … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Sn was also thought to have a functional component, as its deficiency leads to amelioration of murine autoimmune neuropathy [22]. However, Kidder et al demonstrated that in NZB/NZW F1 mice, Sn-deficiency did not reduce LN severity or delay disease progression [23•]. Therefore, while Sn may have a role as a biomarker for disease severity in LN, it will not necessarily serve as a future therapeutic target.…”
Section: Pathogenesis Of Lupus Nephritismentioning
confidence: 99%
“…Sn was also thought to have a functional component, as its deficiency leads to amelioration of murine autoimmune neuropathy [22]. However, Kidder et al demonstrated that in NZB/NZW F1 mice, Sn-deficiency did not reduce LN severity or delay disease progression [23•]. Therefore, while Sn may have a role as a biomarker for disease severity in LN, it will not necessarily serve as a future therapeutic target.…”
Section: Pathogenesis Of Lupus Nephritismentioning
confidence: 99%
“…Whereas CD169 deficiency is sufficient to ameliorate murine autoimmune neuropathy, suggesting a functional contribution of this molecule to autoimmune pathologies [68], LN severity and disease progression in a murine model of SLE were unaffected by CD169 deficiency [69]. However, in SLE, CD169-expressing monocytes within the glomeruli correlate with LN disease severity [70], suggesting a utility for this molecule not as a therapeutic target for, but as a biomarker of, LN disease severity [71].…”
Section: Lupus Nephritismentioning
confidence: 99%
“…Many of the above disease associations may reflect exposure of macrophages to interferons rather than being causally related. Indeed, in the BWF1 murine model of spontaneous systemic lupus erythematosus, there was no influence of Sn deficiency on disease severity (45). However, in mouse models of inherited neuropathy (46)(47)(48), autoimmune uveoretinitis (49), and experimental allergic encephalomyelitis (50), Sn-deficient mice exhibited reduced inflammation accompanied by reduced levels of T-cell and macrophage activation.…”
Section: Sialoadhesin (Siglec-1; Cd169)mentioning
confidence: 99%